Out-of-pocket expenditure experienced by couples seeking In Vitro Fertilization (IVF) services at tertiary care facilities in India - Prerana Patil; Akshita Vikani; Deepshikha Sharma; Oshima Sachin; Biju Soman; Bhavani Shankara Bagepally; Renu Tanwar; Vanita Suri; V. Radha; M. Anitha; P. Ramesh; Deepti Shrivastava; et al. (PLoS ONE, 2026)
Objective Out-of-pocket expenditure (OOPE) incurred by infertile couples seeking In Vitro Fertilization (IVF) treatment in selected public and private hospitals in India. Design Cross-sectional observational study. Setting Two private and three public tertiary care hospitals across varied geographical regions of India that provide IVF services. Participants A total of 148 couples undergoing IVF were enrolled via semi-purposive consecutive sampling over a six-month period after providing informed written consent. Primary outcome measures Using validated structured tool, direct health costs (procedures, drugs, diagnostics), non-medical costs (travel, food, lodging), and indirect costs (loss of wages) were explored. Catastrophic health expenditure (CHE) and predictors of OOPE were also assessed. Results The mean OOPE per IVF cycle was ₹1,10,104 (±₹75,503) [~USD 1,321(±906)] in public hospitals and ₹2,30,668 (±₹1,09,556) [~USD 2,768 (±1315)] in private hospitals. The majority of expenses were on drugs and diagnostics. Approximately 30% of couples experienced CHE, with drug costs contributing 55% of total expenditure. Only 5% had insurance coverage, with an average cover of ₹1,00,625 (±35,500) [~USD 1,208 (± 426)]. Over half (58%) relied on external financial support, mostly from friends and family.Couples without insurance had significantly higher OOPE than those with coverage (p=0.029). Higher household income was also linked to increased OOPE (p=0.001). Couples undergoing treatment at private facilities had 7.7 (CI: 2.5-23.15) times higher odds of experiencing CHE compared to public facilities. Lack of insurance coverage was associated with higher odds of CHE, although not significant. Conclusions Couples undergoing IVF in public and private hospitals face substantial financial burdens, often resulting in CHE. This justifies the need to improve access to comprehensive infertility services, including IVF, through public health facilities to meet the demand for this emerging health problem.